Reconstruction of Ratification of Notarial Deeds as Authentic Deeds in the Case of Indigenous People - Kumala, Ida Ayu Ratna; Yusa, I Gede; Marwanto, Marwanto; Jayantiari, I Gusti Agung Mas Rwa (East Asian Journal of Multidisciplinary Research, 2024)
This research uses normative research methods with a statute approach, historical approach, and conceptual approach.  This research aims to find out, examine, and analyze the urgency of legal protection for persons with disabilities against authentic deeds made before a Notary and also to examine and determine the validity of notarial deeds made by persons with disabilities through alternative relevant attestation procedures. The result of this research is that the reconstruction model for the validation of an authentic deed made before a notary for a disabled person follows the provisions of Article 44 of the UUJNP, but this provision must be accompanied or accompanied by at least 2 (two) witnesses who will later make a certificate of testimony (Affidavit) before the notary that he witnessed the disabled person had made the deed before the notary concerned. In essence, the reconstruction of authentic deed attestation is needed to realize the purpose of the law it self, in the form of certainty, justice, and expediency.